The financial structure of startup firms: The role of assets, information, and entrepreneur characteristics - Paroma Sanyal; Catherine L. Mann (Federal Reserve Bank of Boston, 2010)
Using the Kauffman Firm Survey, we examine how characteristics of a startup's assets, information about the startup, and entrepreneur attributes relate to financial structure at inception. Startups with more physical assets or those where the entrepreneurs have other similar businesses are more likely to use external debt in the financial structure since these assets have a high liquidation value. Startups with human capital embodied in the entrepreneur or intellectual property assets have a lower probability of using debt, consistent with the higher asset specificity and lower collateral value of these assets. Startups characterized as small, unincorporated, solo, first-time, or home-office-based are more likely to be financed by self, family and friends, and importantly through credit cards, as these have both highly specific assets and information opacity. More educated founders and non-African American founders are more likely to be financed by external sources. Controlling for other attributes of the startup, the financial structure of women-owned startups does not differ from that of other startups. Hi-tech startups' financial structure differs significantly from that of startups in other business sectors.
Keywords: G32; L26; 330; Unternehmensgründung; Kapitalstruktur